Pembiasaan Kegiatan Infak Jumat Dalam Membentuk Karakter Religius di SD Negeri Wonosari Kabupaten Purworejo - Rimandani Mukharomah; Prawidya Lestari; Nur Rohmah Hayati (Lembaga Pendidikan Hikmatun Najah (LPHN) Blora, 2023)
The purpose of this study was to analyze how the habituation of fifth grade infak Friday activities can shape the religious character of SD Negeri Wonosari as well as the supporting and inhibiting factors. This type of research is Field Research with a qualitative approach. Data collection methods through interviews, observation, documentation. The results showed that Friday infaq activities can foster religious character, namely (1) the value of worship (2) the religious character of caring for others (3) sincerity. Supporters of the implementation of Friday Infaq habituation activities for class V in forming religious character factors at Wonosari Elementary School come from: 1) parents, who play a role by giving money, (2) the school, namely by understanding children's understanding of infaq and its use (3) student self-awareness . The inhibiting factors were: (1) students' self-consciousness, such as students preferring their money to buy snacks, (2) parents of students, such as those who do not agree if their children do infak Friday activities, (3) teachers, such as when the teacher forgot to give a box infaq and when the teacher has assignments outside of school.